Experimental system design for online characterization and performance analysis of PV module under distinguish environmental conditions - Anand, Rahul; K. Chauhan, Yogesh; Yadav, Vinod; Pachauri, Rupendra (EAI Endorsed Transactions on Energy Web, 2020)
This paper is a novel attempt to evaluate the performance of photovoltaic (PV) modules using current-voltage (I-V) and power-voltage (P-V) characteristics. Numerous significant performance parameters, such as open-circuit voltage, shortcircuit current, maximum power point (MPP), fill factor (FF) and efficiency, are evaluated under various environmental conditions during the investigation. In order to capture online solar electrical parameters, a low-budget test rig is developed using Arduino-assisted supporting components and interfaced with the MATLAB Graphical User Interface (GUI) environment to demonstrate experimental I-V and P-V characteristics. The performance assessment is conducted for three naturally available dust samples categorized using types and weights. In addition, reflectors are often used to boost the efficiency of clean and dusty modules for comprehensive comparison. The present study is useful for three aspects: designing a low-cost PV analyser; choosing the location of the solar power plant; and enhancing the efficiency of the current solar plant.
Keywords: photovoltaic system; dust samples; power losses; fill factor; dust effect